Designing of Phantom Head Used in Optical Diagnostics of Brain Injury; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Aristov A. A. Aleksandr Aleksandrovich; Timchenko K.; Novoseltseva A.; Kustov D.; Larioshina I. A. Irina Anatolievna (2016, 2016)
Title screen